COVID-19 Seroprevalence in Romania: Insights from a Nationwide Antibody Study - Réka Bodea; Toader Septimiu Voidăzan; Lorand Iozsef Ferencz; Zoltán Ábrám (Epidemiologia, 2025)
Background: Frequency indicators are used by epidemiologists to facilitate public health professionals in estimating the impact of diseases. As of April 2022, Romania had reported 2.8 million confirmed COVID-19 cases to the World Health Organization, equating to a prevalence rate of 13.94%. A more accurate method for assessing the cumulative number of cases is the use of seroprevalence studies. This study retrospectively evaluates infection trends in Romania to enhance understanding of the virus’s spread and may support future comparative analyses of public health responses and community-level immunity. Methods: We analyzed 51,533 qualitative test results for high-affinity IgG antibodies targeting the SARS-CoV-2 nucleocapsid protein. Results: The largest proportion of tested individuals (59.4%) was aged 18–49 years. Among all serological tests, 18,980 were positive, corresponding to an adjusted seroprevalence rate of 40%. Conclusions: During the second year of the pandemic, seropositivity rates were highest among young adults, particularly in the western regions, and lowest among children and adolescents. These findings point out variations in exposure across age groups and geographic areas.